Birds of Parque Nacional do Caparaó, Atlantic Forest, southeastern Brazil - Carolina Demetrio Ferreira (Pensoft Publishers, 2021)
Parque Nacional do Caparaó is located in the Serra do Caparaó in the southeastern region of Brazil. It lies on the border between the states of Espírito Santo and Minas Gerais. It is a large fragment of Atlantic Forest vegetation, with altitudinal variation from 630 to 2,892 m. We present an annotated list of bird species found in the park based on data collected from 2012 to 2018. We recorded 216 species, including 66 endemic, 22 threatened, and 17 newly recorded species. To complete the list of species, we added data available in several bibliographic sources and digital databases, bringing the total number of bird species in the park to 348 and including 98 endemic and 33 threatened species. This work is the first to present an updated list of birds for the park, and the data presented show the importance of this protected area for conservation of birds in the region.